HLA‐stripped platelets: preclinical developments and clinical outlooks. (25th January 2017) - Meinke, S.; Karlström, C.; Gryfelt, G.; Wikman, A.; Höglund, P.
Abstract : Antibodies to foreign HLA class I can form in patients exposed to allogeneic cells, for example during blood transfusion. During platelet transfusions, these anti‐HLA class I antibodies can bind to transfused platelets and mediate their destruction, causing platelet refractoriness. Providing HLA‐matched platelets is a therapeutic option for immunized patients. However, sometimes HLA‐matched donors cannot be found or are too few, leading to suboptimal treatment and risks of bleedings. An alternative is to strip standard platelets of HLA class I using a brief incubation at low pH. Such HLA‐stripping results in a reduction in HLA class I expression at the surface, followed by loss of reactivity to HLA class I‐specific antibodies. HLA‐stripped platelets therefore have therapeutic potential in platelet refractory patients. In this article, we summarize our recent work on HLA stripping of platelets and discuss how the HLA‐stripping process affects platelet function and interactions with cells of the immune system. We also review earlier clinical case studies in which HLA‐stripped platelets have been used In patients, and discuss concerns and considerations that should be taken into account when testing their efficacy in platelet refractory patients in clinical trials.